(untitled) (Research, Society and Development, 2022)
This is an integrative literature review study, in the qualitative modality, the databases used were the Latin American and Caribbean Health Sciences Literature (LILACS) and Medical Literature Analysis and Retrieval System Online (MEDLINE), using the Health Science Descriptors (DeCS), namely “Coronavirus”, “Risk Factors” and “Pregnancy”. Studies that answered the guiding question, the publication period from 2019 to 2021 and be in Portuguese, English or Spanish were included in this study. Duplicates, integrative reviews, books, letters and articles with previous notes were excluded, thus totaling 10 articles to compose the research analysis. Thus, it was possible to perceive the great increase in the risk of cesarean deliveries, premature deliveries and neonatal hospitalizations, these related to the psychological issues of the binomial, as well as the pandemic favored in the low access to care of pregnant women in the prenatal routine due to the rapid virus spread. In this way, social and routine changes corroborate the emergence of emotional and care fragility of this pregnant woman and puerperal woman in the pandemic period. It is concluded that it was noticeable to identify the various risk factors and the effects that these women faced and face as part of the risk group, it is necessary to reinforce preventive measures, in addition to strengthening new studies and publications ahead of the disease.